Erinnerung im Umbruch Die Fortsetzung, Drucklegung und Ablösung der »Grandes chroniques de France« im 15. und frühen 16. Jahrhundert - Schwitter, Thomas (Pariser Historische Studien, 2022)
The study traces the development of historiography surrounding the rulers in France in the 15th and early 16th centuries. In the first two parts, the focus is on the continuation and printing of the "Grandes Chroniques" in the 15th century up to the replacement of this leading text by the new, humanistically influenced works of Robert Gaguin and Paulus Aemilius. Along the way, numerous stages of development are reconstructed. Moreover, many historiographical works that have hardly been studied so far but were influenced heavily by the "Grandes Chroniques" are also discussed. For a long time during that period, the main topic of French historiography was the French Civil War (1407-1435) and the associated conflict with the English kings. The struggle of various parties for interpretative sovereignty over those decades therefore had a decisive influence on the development of French historiography in the 15th and early 16th centuries, which will be examined in the third part.